(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To determine the improvement of the quality of life in patient of BPH after transurethral resection of prostate. Methods: A total of 102 of patients complaining lower urinary tract symtoms due to Benign prostatic hyperplasia (BPH). Each of the patient was followed up at 8 weeks (1st visit), 16 weeks (2nd visit) and 24 weeks (3rd visit) after transurethral resection of prostate (TURP). Before TURP for base line study of each patient was evaluated by history, physical examination, digital rectal examination (DRE), International Prostate Symptoms Score (IPSS), Quality of Life Score (QOL), Urinalysis, volume of the prostate and post voidal residual urine (PVR) were determined by ultrasonogram. Improvement of lower urinary tract symptoms and quality of life was determined using IPSS. Improvement was based on the changes from base line in symptoms,urinary flow rate, amount of post voidal residual urine and quality of life.Urine flow rate was measured by uroflowmetry as peak urinary flow rate (Qmax), voiding time and voided volume and was considered valid only if the voided volume was >200 ml. Symptoms were assessed using IPSS & consisting of seven symptoms (frequency, nocturia, urge in continence, urgency, hesitancy, terminal dribbling and sense of incomplete evacuation) that were graded from 0-5. An overall symptoms score was calculated. Result: 102 cases were evaluated by history, physical examination, digital rectal examination (DRE), international prostate symptom scoring (IPSS), quality of life (QOL) scoring, uroflowmetry, post voided residual urine (PVR) and volume of prostate by USG and serum prostate specific antigen (PSA). Cases were selected between 60-75 years. In group-A, among 42 cases (41.2%) <65 years and group-B, 60 cases (58.80%) > 65 years. Age of the patients of each group was compared with IPSS, PVR, Qmax and QOL. Before TURP, IPSS range 17-25 and mean 21.61+2.43, after TURP, range 0-7 and mean 4.27+1.71). There was significant correlation between the IPSS obstructive scores and Qmax at base line (P=<0.001), while correlations at the 1st, 2nd and 3rd follow up significant. There was also a significant correlation between IPSS obstructive score and PVR, and quality of life. After TURP, the IPSS Score showed significant improvements in urinary symptoms with the IPSS showing more significant change for obstructive symptoms. A significant improvement of IPSS was found from 2 months to 6 months follow up after TURP. The change was tested using “paired student ‘t’ test”. Mean quality of life was 5.01+0.64 at base line, which became 0.60+0.91 at end point and therefore change of mean QOL was -4.41+0.93 ml. A significant improvement QOL after transurethral resection of the prostate. The change was test using ‘Paired Student‘t’ test’. The change was found significant (P=<0.001). Conclusion: Transurethral resection of prostate resolves obstructive symptoms, rapid improvement of urinary flow rate and quality of life that is why it is considered as gold standard treatment for moderate to severe symptomatic BPH patients. Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.3-8